Church, state and the ethical imagination : a phenomenological study of Christian, cultural and constitutional value clashes in South Sudan - Manyok, Zechariah (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.